Oncological effects and complications of salvage cryotherapy for radio-recurrent prostate cancer: a systematic review and meta-analysis - Zhu, Shengyu; Liu, Jianjiang; Shen, Bin; Xu, Huali; Zhong, Wei; Jin, Sheng (Frontiers in Oncology, 2025)
BackgroundCryotherapy plays a crucial role in managing radio-recurrent prostate cancer (PCa) after initial treatment. This study aims to provide a comprehensive review of its effectiveness and associated complications.MethodsA systematic review was conducted using PubMed and EMBASE databases up to June 2024, focusing on recurrence-free survival (RFS) with salvage cryotherapy across various subgroups. Severe complications were also assessed. Survival curves were reconstructed using WebPlotDigitizer and a newly developed Shiny application. The incidence of complications was summarized with a 95% confidence interval (CI) using a random-effects model. Complications were evaluated using the Clavien-Dindo Scale (CDS).ResultsThirty-six studies were included, with 15 papers (3174 patients) contributing to survival curve reconstruction. Among 1593 patients treated with salvage cryotherapy, the median RFS was 56.7 months, with 2-, 3-, and 5-year rates of 67.6%, 59.5%, and 47.3%, respectively. Factors associated with better RFS included a longer time from primary treatment to salvage therapy (TRS) [> 70 months vs. < 70 months, hazard ratio (HR) (95% CI):0.75(0.58-0.97), p=0.031], lower pre-salvage prostate-specific antigen (PSA) levels [< 5 ng/mL vs. > 5 ng/mL, HR (95% CI):0.78 (0.65-0.93), p=0.005], salvage whole-gland cryotherapy (SWC) [whole vs. focal, HR (95% CI):0.45 (0.37-0.56), p < 0.001], neoadjuvant androgen deprivation therapy (ADT) [Yes vs. No, HR (95% CI):0.79 (0.69-0.89), p < 0.001], and higher adjuvant ADT usage [16.5-34.2% vs. 0-10.5%, HR (95% CI):0.47(0.39-0.56), p < 0.001]. Concerning severe complications, 78 out of 876 patients (8.9%, 95% CI: 7-11) experienced genitourinary (GU) events, 53 out of 633 patients (8.5%, 95% CI: 6-11) suffered from urinary incontinence, 15 out of 493 patients (3.0%, 95% CI: 2-5) had urethral sloughing/stenosis, and 6 out of 522 patients (1.1%, 95% CI: 0-2) developed recto-urethral/vesical fistula. No cases of severe haematuria, urinary tract infection, or urinary retention were reported.ConclusionsCryotherapy demonstrates a favorable safety profile and significant RFS benefits for salvage treatment of radio-recurrent PCa. Longer TRS, lower pre-salvage PSA, SWC, and peri-salvage ADT usage appear to be promising prognostic factors for RFS. However, confirmation of these findings requires randomized controlled trials (RCTs) due to the low evidence levels and study heterogeneity.